2023
DOI: 10.1021/acs.jpcc.3c03512
|View full text |Cite
|
Sign up to set email alerts
|

Band-Gap Energy and Electronic d–d Transitions of NiWO4 Studied under High-Pressure Conditions

Abstract: We report an extensive study of the optical and structural properties of NiWO4 combining experiments and density functional theory calculations. We have obtained accurate information on the pressure effect on the crystal structure determining the equation of state and compressibility tensor. We have also determined the pressure dependence of the band gap finding that it decreases under compression because of the contribution of Ni 3d states to the top of the valence band. We report on the sub-band-gap optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…The only slight difference between calculations and experiments is that according to calculations the unit-cell parameters are slightly less compressible than in experiments. Such discrepancies are within the typical discrepancies between experiments and computational results in other wolframites . It might be possible to overcome them using different exchange-correlation functionals in calculations, but a systematic study of the optimum functional for FeWO 4 is beyond the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The only slight difference between calculations and experiments is that according to calculations the unit-cell parameters are slightly less compressible than in experiments. Such discrepancies are within the typical discrepancies between experiments and computational results in other wolframites . It might be possible to overcome them using different exchange-correlation functionals in calculations, but a systematic study of the optimum functional for FeWO 4 is beyond the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their bulk modulus, an external pressure of 10 GPa causes a 10% change in the unit-cell volume. Consequently, the electronic, magnetic, vibrational, and elastic properties can be dramatically altered. , However, it is known that several AWO 4 wolframite-type compounds do not undergo phase transitions up to pressures of around 20 GPa. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4(c)), we have found that it can be described by a third-order Birch-Murnaghan equation of state (BM EoS). 39 According to the fits, the experimental unit-cell volume at zero pressure, bulk modulus, and its pressure derivative are V 0 = 290.5(2) Å 3 , B 0 = 155(6) GPa, and B′ 0 = 6.6 (7), respectively, while the corresponding theoretical values are V 0 = 294.8(2) Å, B 0 = 143(5) GPa and B′ 0 = 4.4 (6). The…”
Section: Papermentioning
confidence: 99%
“…The high-pressure (HP) behaviour of MTO 4 bimetal oxides has been the focus of research interest during the last two decades. 1,2 The main objects of study have been phosphates, 3,4 vanadates, 5,6 tungstates, 7,8 molybdates, 9,10 chromates, 11,12 niobates, 13,14 and tantalates. 15,16 On the other hand, a group of compounds that have been barely studied under HP are orthoantimonates, among which only BiSbO 4 has been studied.…”
Section: Introductionmentioning
confidence: 99%